The Effect of Food Quality, Price Fairness and Physical Environment on Customer Satisfaction in Fast Food Restaurants in Kathmandu - Bhandari, Anamol (Nepalese Journal of Business, 2025)
This study examines the effect of food quality, price fairness and physical environment on customer satisfaction in fast food restaurants in Kathmandu. Customer satisfaction is selected as the dependent variable. Similarly, price, food quality, service quality, service time and physical environment are selected as the independent variables. This study is based on primary data with 123 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing food quality, price fairness and physical environment on customer satisfaction in fast food restaurants in Kathmandu. The study showed that service quality has a positive impact on customer satisfaction. It means that increase in service quality leads to increase in customer satisfaction. Similarly, food quality has a positive impact on customer satisfaction. It means that increase in food quality leads to increase in customer satisfaction. Moreover, the service time has a positive impact on customer satisfaction. It indicates that better the service time, higher would be the customer satisfaction. In addition, the physical environment has a positive impact on customer satisfaction. It indicates that better physical environment leads to increase in customer satisfaction. Likewise, the price has a negative impact on customer satisfaction. It means that increase in price leads to decrease in customer satisfaction.